klee04
contestada

HELP!! WILL BE MARKED BRAINLIEST!! 1. Justify each step in solving the equation 4x = 7(x - 3) by
writing areason for each statement
+Answer:
Statement
Reason
1. 4x = 7(x - 3)
1. given
2.
2. 4x =7x-21
3. - =-3x 21
3.
4.
4. X = 7

Respuesta :

Answer: If u divide both sides by 3 you get the value o x 2 answer: Combine terms by transporting. The equation becomes 4x -7x = -21

Step-by-step explanation: 1. 4x=7(x-3) -----> Start with the given.

2. 4x=7x-21 -----> Distribute 7 by multiplying it to the individual terms inside the parenthesis. 7(x) - 7(3) = 7x -21

3. -3x=-21   ------> From step 2, combine like terms by transposing. The equation becomes 4x - 7x = -21. Simplifying, it becomes -3x = -21

4. x = 7 -----> Divide both sides by -3, you get the value o x.

Hope this helps :)

ACCESS MORE